1999
DOI: 10.1073/pnas.96.24.13950
|View full text |Cite
|
Sign up to set email alerts
|

Granzymes are the essential downstream effector molecules for the control of primary virus infections by cytolytic leukocytes

Abstract: Analysis of perforin-deficient mice has identified the cytolytic pathway and perforin as the preeminent effector molecule in T cellmediated control of virus infections. In this paper, we show that mice lacking both granzyme A (gzmA) and granzyme B (gzmB), which are, beside perforin, key constituents of cytolytic vesicles, are as incapable as are perforin-deficient mice of controlling primary infections by the natural mouse pathogen ectromelia, a poxvirus. Death of gzmA؋gzmB double knockout mice occurred in a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
174
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 195 publications
(184 citation statements)
references
References 47 publications
(56 reference statements)
8
174
1
Order By: Relevance
“…GzmA À / À and GzmB À / À mice each showed only marginally increased susceptibility to ectromelia in comparison with WT; however, GzmA À / À B À / À mice were highly susceptible, similar to Pfp À / À mice. 29 This demonstrates the importance of different Gzms cooperatively mediating alternative pathways to cell death. Consistent with previous reports showing modest cytotoxic activity for mGzmA, but none for its human counterpart, 10 we found that proteolytically active recombinant human GzmA (hGzmA) was very poorly cytotoxic when administered with Pfp (Supplementary Figure S7).…”
Section: Discussionmentioning
confidence: 93%
“…GzmA À / À and GzmB À / À mice each showed only marginally increased susceptibility to ectromelia in comparison with WT; however, GzmA À / À B À / À mice were highly susceptible, similar to Pfp À / À mice. 29 This demonstrates the importance of different Gzms cooperatively mediating alternative pathways to cell death. Consistent with previous reports showing modest cytotoxic activity for mGzmA, but none for its human counterpart, 10 we found that proteolytically active recombinant human GzmA (hGzmA) was very poorly cytotoxic when administered with Pfp (Supplementary Figure S7).…”
Section: Discussionmentioning
confidence: 93%
“…One example being poxvirus-encoded serine protease inhibitors that can severely curtail cytolytic effector functions, most probably by inhibiting Fas-mediated and caspase-facilitated PS exposure, resulting in uncontrolled viral spread. 36 This diversity in effector function of cytolytic pathways will also be to the host's benefit in tumor elimination.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44] In vivo, grB À/À knockout mice have shown enhanced susceptibility to mouse cytomegalovirus (MCMV), ectromelia virus, reduced graft versus host disease, and a reduced ability to clear allogeneic tumors. [45][46][47][48] However, in various other models, GrB-deficient mice remain competent at viral and tumor clearance, which is likely a reflection of Gr redundancy in these animals. 49 Granzyme H. GrH was identified through screening cDNA libraries derived from cytotoxic cells.…”
Section: Mechanisms Of Cytotoxicity and Physiological Roles Of Grsmentioning
confidence: 99%